2010
DOI: 10.1002/pro.430
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the apo and ATP bound Mycobacterium tuberculosis nitrogen regulatory PII protein

Abstract: PII constitutes a family of signal transduction proteins that act as nitrogen sensors in microorganisms and plants. Mycobacterium tuberculosis (Mtb) has a single homologue of PII whose precise role has as yet not been explored. We have solved the crystal structures of the Mtb PII protein in its apo and ATP bound forms to 1.4 and 2.4 Å resolutions, respectively. The protein forms a trimeric assembly in the crystal lattice and folds similarly to the other PII family proteins. The Mtb PII:ATP binary complex struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Based on sequence comparison methods (see Methods), the fourth member of the novel four-gene cluster reveals remote but statistically detectable homology to the ubiquitous PII signal-transducer proteins. An analysis of these carboxysome-associated PII-like proteins reveals divergent PII-like motifs (B-loop and C-loop) thought to be critical for nitrogen regulatory PII activity 7174 , suggesting a distinct or specialized function. Estimates of evolutionary divergence place the carboxysome-associated PII-like proteins in a distinct clade (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on sequence comparison methods (see Methods), the fourth member of the novel four-gene cluster reveals remote but statistically detectable homology to the ubiquitous PII signal-transducer proteins. An analysis of these carboxysome-associated PII-like proteins reveals divergent PII-like motifs (B-loop and C-loop) thought to be critical for nitrogen regulatory PII activity 7174 , suggesting a distinct or specialized function. Estimates of evolutionary divergence place the carboxysome-associated PII-like proteins in a distinct clade (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2) is similar to structures reported for well-studied nrPII proteins and to a structure deposited in the PDB (2CZ4) for a PII-like protein from Thermus thermophilus . 7478 PII proteins are homotrimeric with nucleotide binding sites at three identical subunit interfaces. The CPII secondary structure consists of two consecutive but interdigitated β-α-β motifs connected by a flexible loop that comprises the so-called “T-loop”.…”
Section: Resultsmentioning
confidence: 99%
“…The amtB gene is frequently co-transcribed with glnK , strongly suggesting that these proteins function together, 16 and direct evidence for the interaction of GlnK and AmtB has been provided by crystal structure studies 17,18 . Comparing the structure of M. tuberculosis GlnK (PII) (apo- and ATP-bound forms) with the E. coli GlnK:AmtB complex structure suggests that M. tuberculosis GlnK (PII) could form a complex with AmtB in a similar manner 14 . These studies have also shown that the M. tuberculosis GlnK (PII) folds similarly to other PII family proteins 19 and that ATP binding is vital for complex formation with AmtB 14 …”
Section: Introductionmentioning
confidence: 99%
“…Comparing the structure of M. tuberculosis GlnK (PII) (apo- and ATP-bound forms) with the E. coli GlnK:AmtB complex structure suggests that M. tuberculosis GlnK (PII) could form a complex with AmtB in a similar manner 14 . These studies have also shown that the M. tuberculosis GlnK (PII) folds similarly to other PII family proteins 19 and that ATP binding is vital for complex formation with AmtB 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation